The bacterial and archaeal communities of flies, manure, lagoons, and troughs at a working dairy - Tawni L. Crippen; Dongmin Kim; Toni L. Poole; Sonja L. Swiger; Robin C. Anderson (Frontiers in Microbiology, 2024)
BackgroundFundamental investigations into the location, load, and persistence of microbes, whether beneficial or detrimental, are scarce. Many questions about the retention and survival of microbes on various surfaces, as well as the load necessary for spread, exist. To answer these questions, we must know more about where to find various microbes and in what concentrations, the composition of the microbial communities, and the extent of dissemination between various elements. This study investigated the diversity, composition, and relative abundance of the communities associated with manure, lagoons, troughs, house flies, and stable flies present at a dairy, implementing two different free-stall management systems: flow-through and cross-vent. Shotgun metagenomics at the community level was used to compare the microbiomes within the dairy, allowing confident interpretation at the species level.ResultsThe results showed that there were significant difference in microbial composition between not only each of the dairy elements but also management styles. The primary exceptions were the microbiomes of the house fly and the stable fly. Their compositions heavily overlapped with one another, but interestingly, not with the other components sampled. Additionally, both species of flies carried more pathogens than the other elements of the dairy, indicating that they may not share these organisms with the other components, or that the environments offered by the other components are unsatisfactory for the survival of some pathogens..ConclusionThe lack of overlapping pathogen profiles suggests a lack of transfer from flies to other dairy elements. Dairy health data, showing a low incidence of disease, suggests minimal sharing of bacteria by the flies at a level required for infection, given the health program of this dairy. While flies did carry a multitude of pathogenic bacteria, the mere presence of the bacteria associated with the flies did not necessarily translate into high risk leading to morbidity and mortality at this dairy. Thus, using flies as the sole sentinel of dairy health may not be appropriate for all bacterial pathogens or dairies.